Harmonisasi Sosial Pada Perilaku Keagamaan Masyarakat Buddhis dan Muslim Dalam Kajian Upali Sutta - Sukarti Sukarti (STABN RADEN WIJAYA WONOGIRI, 2023)
This study aims: To describe the religious behavior of Buddhists and Muslims; To analyze the social harmonization formed in the religious behavior; To analyze the factors that cause of social harmonization in the religious behavior. This research is a qualitative research with a case study approach. Data collection techniques using observation, interviews, and documentation. Data analysis used the Milles and Huberman models. The data validity test using triangulation techniques and sources. The results of the study describe the Buddhists and Muslims in Sodong hamlet have realized that worship according to religion and belief is a basic need for religious people. Harmony is seen in gotong-royong, together in celebration of religious ceremonies, mutual support and giving, anjangsana and the formation of togetherness groups in the field of arts and culture. The harmony that grows in the plural society in Sodong hamlet is due to the principle that is believed together with the slogan